Association between local treatment modalities and event-free survival, overall survival, and local recurrence in patients with localised Ewing Sarcoma. Report from the Ewing 2008 trial - Heesen, Philip; Ranft, Andreas; Bhadri, Vivek; Brichard, Benedicte; Collaud, Stephane; Cyprová, Soňa; Eich, Hans; Ek, Torben; Gelderblom, Hans; Hardes, Jendrik; Haveman, Lianne; Jabar, Susanne; et al. (European journal of cancer, 2023)
BACKGROUND: Local treatment is a crucial element in the standard of care for Ewing sarcoma (EWS). While systemic treatment is improved in randomised clinical trials, local treatment modalities are discussed controversially. We analysed the association between local therapy and event-free survival (EFS), overall survival (OS), and local recurrence (LR) in prospectively collected data of patients with localised EWS. PATIENTS AND METHODS: We analysed data from the international Ewing 2008 study registered between 2009 and 2019 in 117 centres. After induction chemotherapy, patients received surgery, radiotherapy, or a combination thereof. We performed Cox regression, conducted propensity score-weighted sensitivity analysis, and performed subgroup analyses. Hazard ratios (HRs) and 95% confidence intervals are reported. RESULTS: We included 863 patients with localised EWS (surgery alone: 331, combination therapy: 358, definitive radiotherapy: 174). In patients treated with combination therapy compared to surgery alone, EFS HR was 0.84 (0.57-1.24; p = 0.38), OS HR was 0.84 (0.57-1.23; p = 0.41), and LR HR was 0.58 (0.26-1.31; p = 0.19). Hazards of any event were increased in patients treated with definitive radiotherapy compared to surgery only, HR 1.53 (1.02-2.31; p = 0.04). Patients with poor responses to chemotherapy benefitted from combination therapy over definitive surgery with an EFS HR 0.49 (0.27-0.89; p = 0.02). Patients with pelvic tumours benefitted from combination therapy over surgery only regarding LR, HR 0.12 (0.02-0.72; p = 0.02). CONCLUSION: Patients with poor responses to chemotherapy benefitted from radiotherapy added to surgery. In the whole group, radiotherapy alone as opposed to surgery alone increased the hazards of any event.
Keywords: doba přežití bez progrese choroby; Radiation Oncology; indukční chemoterapie; radiační onkologie; lidé; Ewingův sarkom; Sarcoma, Ewing; kombinovaná terapie; Combined Modality Therapy; Progression-Free Survival; Induction Chemotherapy; Humans